New species of the genera Acronicta Ochsenheimer, 1816 and Craniophora Snellen, 1867 from China with notes on synonymy and checklist (Lepidoptera, Noctuidae: Acronictinae) - Han, H. L.; Kononenko, V. S. (Zootaxa, 2010)
Two new species of the genera Acronicta Ochsenheimer, 1816 and Craniophora Snellen, 1867 (A. naxi, sp. n. and C. draudti, sp. n.) are described from China. The adults and male and female genitalia are illustrated and compared to allied taxa. In addition, the following new synonymies are introduced: Acronicta lilacina (Hampson, 1914) =succedens Draudt, 1937, syn. n.; A. pulverosa (Hampson, 1909) =expergita Draudt, 1937, syn. n.; A. albistigma (Hampson, 1909) =cavillatrix Draudt, 1950, syn. n.; A. digna (Butler, 1881) =agnata Draudt, 1937, syn. n. =metaxantha Hampson, 1909, syn. n.; A. lutea (Bremer & Grey, 1852) =metaxantha funesta Draudt, 1950, syn. n.; Acronicta cinerea (Hufnagel, 1766) =korlana Draudt, 1931 =cinerascens Kozhanchikov, 1950. Lectotypes for A. cavillatrix Draudt, 1937, A. metaxantha funesta Draudt, 1950, Craniophora tapaishana Draudt, 1950, C. simillima Draudt 1950 and C. ligustri gigantea Draudt, 1937 are designated, and preliminary synonymic checklists of Acronicta and Craniophora in China are presented.